EXPLORING UNIVERSITY STUDENTS EXPERIENCES USING CHATGPT TO SUPPORT LEARNING - Aulia Nurhaliza; Nurbaety Rahma; Nusantari (POLITEKNIK LP3I JAKARTA, 2026)
This study looks into how students use ChatGPT to help them with their learning. A qualitative method was used to deeply understand what students thought about ChatGPT, the benefit things they found from using it, and the difficulties they face while using it. Data was collected by an online questionnaire distributed using Google Forms to students who had used ChatGPT for their assignments. The results show that ChatGPT helps students learn better, learn complicated topics, come up with new ideas, and finish their assignments more effectively. Participants also mentioned that ChatGPT provides quick and easy answers, which makes it a useful extra resource for learning. Some people also expressed concerns about how accurate the information was, especially since it was mostly created by AI.There was a worry that people might rely too much on this content without checking if it's correct. It was suggested that everyone should use their own thinking skills to verify the answers they find. This study finds that ChatGPT can be useful for students in college, but it also reminds us that it's important to use digital tools carefully and to approach AI in a responsible manner.